"Give Me Proof": A Covert but Coercive Form of Non-partner Sexual Violence Contributing to Teen Pregnancy in Haiti and Opportunities for Biopsychosocial Intervention. Issue 7 (8th August 2020) - Rahill, Guitele J.; Joshi, Manisha; Zlotnick, Caron; Lamour, Sabine; Beech, Haley; Sutton, Amber; Burris, Cameron; Paul, Phycien
ABSTRACT: Adolescent girls in low-resource settings account for over 7.3 million births annually (generally unplanned). Unplanned teen pregnancies are increasing in low-resource settings. As part of a funded Round 20 Grand Challenges Exploration project (Healthy Minds for Adolescent Mothers), we investigated unplanned teen pregnancies in Haiti's Cité Soleil shantytown, teens' biopsychosocial challenges, and desirable interventions. Key stakeholders (N = 23): pregnant teens (13-17-year-olds, n = 8; 18-19-year-olds, n = 8) and health providers (18 or older, n = 7), participated by age group and role in focus groups (FGs). ATLAS.ti facilitated the analysis of transcribed FG audio recordings. Ninety-four percent (n = 15) of teens reported "Banm prèv, " translated "Give me proof, " as a cause of their unplanned pregnancies. Banm prèv describes when teens are propositioned by men who demand proof of their unpretentiousness or virginity. A subtle, covert, locally unchallenged phenomenon that is supported by damaging gender norms, Banm prèv constitutes an illusionary choice between teens' yielding non-consensual control of their bodies and the tacit alternative of gang rape. Banm prèv underscores teens' difficulty discerning consensual from coerced sex. Associated unplanned pregnancies occasion guilt, shame, stigma, depression, anxiety, and trauma in teens. Cité Soleil teens need contextually relevant, community-supported, age-appropriate interventions that challenge existing norms, build on cultural strengths, and include comprehensive sexuality education, including knowledge of reproductive rights. A traditional, contextually familiar, engaging, and humorous story-telling tradition, i.e., krik-krak, packaged in video format, is a useful framework for interventions to reduce depressive symptoms, stress, and anxiety for Cité Soleil teens experiencing unplanned pregnancies.